THE EFFECT OF TRUST, SECURITY, QUALITY OF SERVICE, PERCEPTION OF RISK AND PRICE ON ONLINE PURCHASE DECISIONS - Hardoko Hardoko (UPMI Management, 2022)
This study aims to determine the effect of trust, security, service quality, perception of risk and price on online purchasing decisions. Data was obtained by distributing questionnaires to 105 respondents. The results showed that the results of the t test, trust, perception of risk and price had a positive and significant effect on online purchasing decisions. Meanwhile, security and service quality variables have a positive and insignificant effect on online purchasing decisions. Based on the results of the F statistical test using analysis of variance or ANOVA, it can be seen that the significance value (0.000 < 0.05) which means significant, it can be concluded that the variables of trust (x1), security (x2), service quality (x3), perceptions of risk (x4) and price (x5) simultaneously (simultaneously) have an influence on online purchasing decision variables.